Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Population density–range size relationship revisited - Maria Novosolov; Gordon H. Rodda; Alexandra C. North; Stuart H. M. Butchart; Oliver J. S. Tallowin; Alison M. Gainsbury; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim The species population density–range size relationship posits that locally abundant species are widely distributed. However, this proposed pattern has been insufficiently tested. The few tests conducted were usually limited in scale and gave conflicting results. We tested the generality of the positive population density–range size relationship. We then studied whether similar environmental niche requirements are correlated with range size and with population density to search for mechanisms driving the hypothesized link between population density and range size. Location Worldwide. Methods We collected data on population density, range size and environmental niche for a global dataset of 192 lizard, 893 bird and 350 mammal species. Assessing the relationship between population density and range size and environmental niche parameters, we corrected for phylogenetic relationships, body mass, diet and study area. Results Our findings reveal that density had a weak negative correlation with bird range size and was unrelated to lizard and mammal range size. These trends were consistent at the global scale and across the biogeographical realms. Range size was related to relatively similar environmental niche parameters in all groups. Population density, however, was explained by taxon‐specific factors and was therefore unrelated to range size by common causation. Main conclusions We suggest that the positive relationship between population density and range size identified in previous studies might be an artefact arising through incomplete sampling of range sizes. Our results indicate that the mechanisms shaping population density and range size may be independent.

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

The bioinvasion of Guam: inferring geographic origin, pace, pattern and process of an invasive lizard (Carlia) in the Pacific using multi-locus genomic data - Christopher C. Austin; Eric N. Rittmeyer; Lauren A. Oliver; John O. Andermann; George R. Zug; Gordon H. Rodda; Nathan D. Jackson (Biological Invasions, 2011)

Guide to Hydrological Practices - John C. Rodda (Hydrological Sciences Journal, 2011)

Managing and Transforming Water Conflicts edited by Jerome Delli Priscolli & Aaron T. Wolf - John C. Rodda (Hydrological Sciences Journal, 2010)

A comparative study of the magnitude, frequency and distribution of intense rainfall in the United Kingdom - John C. Rodda; Max A. Little; Harvey J. E. Rodda; Patrick E. McSharry (International Journal of Climatology, 2010)
During the 1960s, a study was made of the magnitude, frequency and distribution of intense rainfall over the United Kingdom, employing data from more than 120 daily read rain gauges covering the period 1911 to 1960. Using the same methodology, that study was recently updated utilizing data for the period 1961 to 2006 for the same gauges, or from those nearby. This paper describes the techniques applied to ensure consistency of data and statistical modelling. It presents a comparison of patterns of extreme rainfalls for the two periods and discusses the changes that have taken place. Most noticeably, increases up to 20% have occurred in the north‐west of the country and in parts of East Anglia. There have also been changes in other areas, including decreases of the same magnitude over central England. The implications of these changes are considered. Copyright © 2009 Royal Meteorological Society

Incorporation time of oxytetracycline into calcified structures of the elasmobranch Heterodontus portusjacksoni - C. Izzo; K. Rodda; T. Bolton (Journal of Fish Biology, 2007)
The time taken for oxytetracycline to be incorporated as an intense, discrete band was determined by examining vertebrae and dorsal fin spines of Heterodontus portusjacksoni that were injected with oxytetracycline 2–180 days post‐treatment. Oxytetracycline was visible in dorsal fin spines 2 days after treatment and 3 days after treatment in sectioned vertebrae. A distinct mark could not be identified in unsectioned vertebrae.